Acute Lung Oedema in Severe Pre-eclampsia: Advanced Management and Anesthetic Interventions - Hotabilardus, Nusi Andreas; Anggraeni, Novita (Faculty of Medicine-Universitas Airlangga, 2025)
Introduction: Acute Lung Oedema (ALO) during pregnancy is an uncommon but potentially life-threatening condition, particularly when associated with severe pre-eclampsia. This critical obstetric emergency requires prompt recognition and comprehensive management to prevent adverse maternal and fetal outcomes. Objective: This report aims to highlights the management of a complex case of ALO in a pregnant patient with severe pre-eclampsia, underscoring the essential role of multidisciplinary collaboration, evidence-based protocols, and individualized care in achieving favorable outcomes. Case Report: A 30-year-old woman at 29–30 weeks gestation presented with significantly reduced consciousness and severe shortness of breath. Clinical examination revealed hypertension, tachycardia, and profound hypoxemia, with radiological evidence of pulmonary oedema. The diagnosis included severe-feature pre-eclampsia complicated by acute respiratory distress syndrome (ARDS) secondary to ALO. Endotracheal intubation was used to protect the mother's airway, mechanical ventilation was used to help her get enough oxygen, and her blood pressure and heart rate were stabilized right away. Fluid therapy was carefully monitored to avoid exacerbating pulmonary oedema. Obstetric management prioritized delaying delivery until maternal stabilization was achieved. A surgical intervention under general anesthesia resulted in the delivery of a moderately distressed neonate. Postoperative care in the intensive care unit included continued mechanical ventilation, sedation, and meticulous fluid management. Gradual stabilization allowed for successful weaning off ventilatory support, extubation, and transfer to a general hospital ward. Discussion: Management strategies were guided by the ABCDE principle, targeting reductions in left ventricular preload and afterload, adequate oxygenation, and infection prevention. The case emphasizes the value of early diagnosis, prompt intervention, and interdisciplinary collaboration involving obstetricians, intensivists, and anesthetists. Conclusion: This case illustrates the importance of early recognition, swift intervention, and tailored care in managing ALO associated with severe pre-eclampsia. Comprehensive, team-based approaches are critical for optimizing maternal and neonatal outcomes in such high-risk scenarios.